Ab initio and experimental study of sulphur/samarium codoped-TiO2 and its visible light photocatalytic activity towards the degradation of orange II dye - Moro Haruna; Charles Kwame Bandoh; Francis Opoku; Eric Selorm Agorku (Next Sustainability)
Recent research efforts have been focused mostly on using semiconductor photocatalysts to degrade hazardous organic contaminants from wastewater. Numerous nanomaterials have thus been investigated and applied to the treatment of wastewater. In this work, a series of samarium (Sm) and sulphur (S) codoped Titanium dioxide (TiO2) photocatalysts have been prepared using the coprecipitation method for the photocatalytic degradation of orange II dye in wastewater. Moreover, the experimental findings were confirmed by First-Principles Density Functional Theory (DFT) calculations. Analytical techniques such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), diffuse reflectance spectroscopy (DRS), UV-Visible spectrophotometry, scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM/EDX), and transmission electron microscopy (TEM) were used to characterized the photocatalysts. The XRD analysis revealed the successful incorporation of S and Sm nanoparticles into the anatase crystal structure of TiO2 with no change in the phase and an average particle size of 9 nm. A theoretical study using DFT revealed an indirect band gap of 3.56 eV as compared to the experimental value of 3.04 eV for virgin TiO2. Codoping significantly influenced the optical properties of the virgin TiO2 and resulted in a redshift in the absorption edge, leading to a bandgap decrease from 3.04 to 2.70 eV. S/Sm3 + modified TiO2 exhibited substantial catalytic activity induced by visible light towards orange II dye relative to the singly doped S-TiO2 or Sm3+-TiO2. The S-TiO2-Sm3+ (0.6 %) photocatalyst obtained the maximum degradation efficiency of 100 % in 2.5 h with a rate constant (k) of 61 × 10−3 min−1. The improved photocatalytic activity of synthesized nanomaterials was credited to the synergistic effects of S and Sm3+ in TiO2, which resulted in a narrow band gap energy, strong absorption of visible light, small crystallite size, and decreased recombination rate.